Brexit and the reform of social security coordination: The UK's metamorphosis from rule maker to rule taker. Issue 2 (June 2020) - Roberts, Simon
This article examines the United Kingdom's negotiating position on the revision of the EU Coordinating Regulations proposed by the European Commission in December 2016, in the context of Brexit and the negotiations on the Withdrawal Agreement. The Withdrawal Agreement contains provisions on the future coordination of social security for UK and EU nationals who have exercised their freedom of movement rights before the end of the transition period. The coordination envisaged by the Withdrawal Agreement has not been sealed at the point of the UK's departure but will continue to evolve and incorporate future changes in the EU Coordinating Regulations, including the reforms contained in the Commission's current legislative proposal. The UK had a seat at the negotiating table until it left the European Union on 31 January 2020, which it used to try to influence the reform of the Coordinating Regulations to reflect its future interests. The article finds that, while the UK participated in negotiating the current revision of the Coordinating Regulations and several of the revisions are in line with its aims, its influence is waning as the UK moves from being a rule maker to a rule taker in Europe.